1D Pyrrolidinium Lead Iodide for Efficient and Stable Perovskite Solar Cells. Issue 4 (28th October 2019) - Pham, Ngoc Duy; Yang, Yang; Hoang, Minh Tam; Wang, Tony; Tiong, Vincent Tiing; Wilson, Gregory Joseph; Wang, Hongxia
Abstract : Due to their superior environmental stability, utilization of low‐dimensional perovskites in organometal halide solar cells (OMHSCs) has seen a sharp increase. Herein, a method to form 1D pyrrolidinium lead iodide (PyPbI3 ) in situ atop photoactive 3D methylammonium lead iodide (MAPbI3 ) using pyrrolidine posttreatment is reported. As compared with 3D MAPbI3, 1D PyPbI3 has a wider bandgap and is more environmentally stable, and it serves as a tunneling contact to mitigate charge carrier recombination and as a robust barrier against environmental degradation when incorporated into OMHSCs. Accordingly, power conversion efficiencies of the resulting MAPbI3 devices are enhanced from an average of 14.86% ± 0.65% to 15.9% ± 0.58% and their shelf‐life stability is significantly prolonged. Abstract : Two is better than one: the role of pyrrolidine in forming an efficient 1D pyrrolidinium lead iodide (PyPbI3 ) interlayer is highlighted. The PyPbI3 plays a dual function in both interfacial passivation and environmental protection of the methylammonium lead iodide (MAPbI3 ) absorber, resulting in the achievement of efficient and stable perovskite solar cells.